Phisiopatology of epilepsy: genetics and environment - Rodríguez Orive, Gretel Laura; Cruz Hechavarria, Sergio Antonio; Machado Reyes, Iliana (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Epilepsy is a group of chronic neurological syndromes derived from alterations in brain functions that present with recurrent paroxysmal crises triggered by abnormal electrical discharges. Objective: describe the updated knowledge related to the genetic bases of the phisiophatology of epilepsy. Material and method: A bibliography revision was made . Methods: analysis-synthesis, induction-decuction, historic-logic were used. Forty- three bibliographic references available at the virtual library of health. Results: the mechanisms which causes electric shocks were described: a decrease of gabaergic inhibitor mechanisms, an increase of stimulating mechanisms mediated by aspartic and glutamic acid and alteration of the transmembrane conduction of sodium and calcium ions. Genes implicated in the neural ionic canal of sodium, potasium, chlorine, calcium(SCN1A, SCN1B, SNC2A, KCNQ2,KCNQ3, CLCN2, CACNA1H), with the receptors for the acetilcoline and GABA neurotransmitter: CHRNA4 and CHRNB2. The gen GRIA3 related to the eye-brain-renal syndrom or Lowe Syndrome. From the epigenetic mechanisms the methylation of DNA and the micro RNA in the epileptgenesis. The pharmacological effectivity according to the neurotrasmitter glutamic(stimulating): topiramate ,talampanel, ketamin; GABA(inhibitor) direct action: benzodiazepines (diazepam, clobazam) and barbiturates(phenobarbital, loreclezol,carisbamate); drugs with indirect action on GABA: acido valproico, tiagabina,vigabatrina (increase of the gabaergig tone by means of the irreversible and suicide inactivation of the enzyme responsable for the metabolism of GABA). Other drugs are: gabapentin, losigamona. Conclusions: It is considered that the genetic bases of the phisiophatology of epilpsy are an important element to understand it is ethiophatogenic, new therapeutic approaches and for the discovery of new drugs.